(untitled) (LACCEI, 2024)
The forms of commercialization of the industrial company have evolved. In such a way that they must know the best option of Supplier Countries. That is why the main objective of this research is to determine the relationship between imports and business intelligence in the company Motor Valle SAC, Chepén in the year 2022. Likewise, 02 variables were worked on (Business Intelligence and Imports), Therefore, a survey was carried out on 20 workers from the international administrative area of ​​the Motor Valle SAC company, in order to obtain information to later process and organize in the SPSS IBM version 25 program. The nature of the non-parametric connection test was Lancer. The instrument has been previously validated by experts and the reliability has been according to Cronbach’s alpha of 0.899 and 0.848. The hypothesis test indicates the coincidence of 0.181 in Spearman’s Rho coefficient, which indicates that it has a positive scale of means, since it is in the interval +0.11 to +0.50, It is concluded in accordance with the general objective of the study that, if there is a positive relationship between business intelligence and importation in the company Motor Valle SAC, Chepén 2022.